Systemic functional linguistics: the perfect match for content and language integrated learning. Issue 3 (16th March 2023) - Llinares, Ana; McCabe, Anne
ABSTRACT: Recent debates on bilingual education/CLIL have insisted on the need to explore common aims across bilingual/multilingual education programmes (CLIL, CBI, immersion) instead of highlighting differences across them (e.g. Cenoz, Genesee & Gorter, 2014). One objective shared by all programmes, regardless of their specificities, is to find the ways in which content and language are best learnt and taught in integration. This involves going beyond the 'focus on form' perspective and looking at language as a meaning-making activity in relation to the genres and registers of specific classroom/academic disciplines. In this issue, Systemic Functional Linguistics (SFL), with its focus on the purposes of language use through texts and contexts, is applied, together with other models, such as Legitimation Code Theory (LCT) or Cognitive Discourse Functions (CDFs), to the understanding of how language and content integration is enacted and its implications for curriculum development, pedagogy and assessment. The studies represent a variety of educational levels, content areas, modes (spoken, written, classroom interaction) and bilingual/multilingual education contexts.